Haitian invasion : after the dust has settled. - VASCIANNIE, Stephen (1997)
Examines the case made by the UN, the US and Jamaica, for an invasion of Haiti to reinstate President Aristide. Argues that there was at least one alternative approach which could have justified military intervention without violating basic tenets of international law. Highlights the way in which the Haitian precedent, as formulated by the UN Security Council may be used to sanction the use of military might without moral or legal foundation.